The specificity of the moral factor in provision of the national security of Belarus - Pavlovskaya, Olga A. (Journal of the Belarusian State University. Sociology, 2022)
In the context of modern social transformations the characteristic features of the manifestation of spiritual and moral values in ensuring the national security of the Belarusian society are revealed. The cultural and historical prerequisites for the formation of the spiritual and moral potential of the Belarusian people, the social and moral risks of the development of national statehood, the actualization of the problems of the moral development of the individual, his self-realization and worldview choice are considered.
Keywords: national security; moral factor; spiritual and moral potential; personal culture; Christian values; national identity; freedom of conscience